مؤشرات تيسير التجارة وانعكاساتها على الصادرات الجزائرية )2022Q4-2007Q1(دراسة قياسية للفترة : Trade facilitation indicators and their implications for Algerian exports standard study for the period 2007Q1-2022Q4 - وفاء رمضاني; جميلة قدة (Journal of North African Economies, 2025)
This study aims to estimate and analyze the impact of soft and hard trade facilitation indicators on the value of total exports in Algeria during the period 2007Q1-2022Q4, using the ARDL time-gap autoregression model.. The study, based on the error correction parameter, concluded that a shock in trade facilitation indicators by one unit will last its impact on the value of total exports for a maximum period of approximately 07 years and 11 months until it returns to its equilibrium and normal position, meaning that the impact of trade facilitation indicators in Algeria on the value of its total exports is very slow, and the results reached according to the joint integration test confirm the existence of a long-term equilibrium relationship between trade facilitation indicators and Algerian exports, which means Improving soft and hard trade facilitation indicators in the long run will increase the value of total exports.